Intravitreal antivascular endothelial growth factors for retinopathy of prematurity in Ibadan: Method of administration - Yewande Olubunmi Babalola (Nigerian Journal of Medicine, 2020)
Purpose: To outline the method of administration of intravitreal antivascular endothelial growth factor (anti-VEGF) for retinopathy of prematurity (ROP) for the purpose of improved eye care among neonates. Background: ROP is a major potential, but largely preventable cause of blindness in the pediatric population. ROP has been shown to be a two-stage event with an initial disruption to normal retinal vessel growth, which is then accompanied by the second stage of vessel development. Preterm infants have undeveloped retinas, with avascular areas at the periphery. Subsequently, as the infant grows, these undeveloped retinas lacking an adequate supply of oxygen then stimulate angiogenic factors for the development of new vessels. Some predisposing risk factors include inappropriate oxygen therapy and lower birth weights. Initially, ROP was documented to be sporadic in most regions of Africa, but due to the recent advancement in medical facilities and personnel training, more preterm babies are surviving, thereby increasing the rate of ROP. Our hospital, the University College Hospital, Ibadan, has been assessing preterm babies for signs of ROP in conjunction with the neonatologists for the last four years, with various stages of ROP being diagnosed and treated. Intravitreal use of anti-VEGF has been accepted as a valuable therapy in preventing the development of advanced cases of ROP. The purpose of this study is to describe the method of administration of this important medication. Conclusion: Intravitreal anti-VEGF may prevent avoidable blindness in babies with ROP. However, to prevent devastating complications, appropriate techniques and the guidelines given in this study should be considered to minimize complications.